2010
DOI: 10.1161/circulationaha.109.879338
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Therapeutic Gas Delivery for Neuroprotection With Echogenic Liposomes

Abstract: Background-Ischemia-related neurological injury is a primary cause of stroke disability. Studies have demonstrated that xenon (Xe) may have potential as an effective and nontoxic neuroprotectant. Xe delivery is, however, hampered by lack of suitable administration methods. We have developed a pressurization-freeze method to encapsulate Xe into echogenic liposomes (Xe-ELIP) and have modulated local gas release with transvascular ultrasound exposure. Methods and Results-Fifteen microliters of Xe were encapsulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 42 publications
0
78
0
Order By: Relevance
“…Despite the detection of strong cavitation at this acoustic pressure, the precise mechanism of NO release and delivery remains unclear. Smith et al describe acoustically driven diffusion at moderate acoustic pressures, 56,57 and other investigators 7,58,59 have postulated that the lipid shell of microbubbles must first be ruptured before cavitation nucleation can occur, liberating encapsulated gas during rapid fragmentation. At a 0.34 MPa pressure exposure, it is likely that NO was released from the bubble liposomes gradually over a number of acoustic cycles.…”
Section: Ultrasound Exposure and Cavitationmentioning
confidence: 99%
“…Despite the detection of strong cavitation at this acoustic pressure, the precise mechanism of NO release and delivery remains unclear. Smith et al describe acoustically driven diffusion at moderate acoustic pressures, 56,57 and other investigators 7,58,59 have postulated that the lipid shell of microbubbles must first be ruptured before cavitation nucleation can occur, liberating encapsulated gas during rapid fragmentation. At a 0.34 MPa pressure exposure, it is likely that NO was released from the bubble liposomes gradually over a number of acoustic cycles.…”
Section: Ultrasound Exposure and Cavitationmentioning
confidence: 99%
“…In a previous study, we have shown intravenous injection of this ELIP formulation with ultrasound release over the carotid artery resulted in an enhanced effect using another bioactive gas encapsulated ELIP. 26 Lipids (5 mg) were mixed in chloroform and vaporized with argon in a 50°C water bath to form a thin film on a glass vial wall. The lipid film was placed under high vacuum (,100 Torr) for 4-6 hours to remove the solvent completely.…”
Section: Preparation Of No-elipmentioning
confidence: 99%
“…We have demonstrated that both pulsed diagnostic ultrasound and continuous ultrasound can be utilized to enhance therapeutic release from ELIP. [25][26][27] In this study, we evaluated NO-ELIP for ultrasoundfacilitated site-specific NO delivery to produce vasodilation affecting vasospasm following subarachnoid hemorrhage. We investigated the vasodilative effects of NO released from NO-ELIP following ultrasound exposure in in vitro, ex vivo, and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations